Natural resource-based recreational activities during COVID-19 pandemic: A local communities perspective in Sabah, Malaysia - Walter Lintangah; Vilaretti Atin; Khalid Nurul Izzah Izati (Penerbit UMS, 2022)
The COVID-19 pandemic has disrupted many activities, including tourism and recreational activities. This study determines the local communities' perceptions of local recreational activities or staycation based on the natural resources in Sabah during the pandemic. Using the convenience sampling method, the questionnaire survey was distributed to respondents through social media and email. Respondents including students, government, and private sectors were from different socio-demographics. Most of them preferred recreational activities based on nature panorama activities, followed by those who chose extreme activities such as hiking, cultural base recreation, river-based activities, leisure vacation and jungle trekking. The respondents opined that recreational activities could generate income for the state's economy. They perceived that the assistance provided by the government could help recover the present state to its original condition. Among the elements that needed special attention and improvement were related to the safety of visitors, the cleanliness of the surrounding recreation sites, the landscape beautification and basic infrastructure facilities. Among the roles that the government could contribute to stimulating and uplifting the tourism and recreation sectors include funding and finance allocation to help the industry players, promotion and publicity, upgrading and maintenance of facilities such as infrastructures and enforcement of related laws and policies. Reviving the local tourism is promising as long as the public observe the state’s Standard Operating Procedure (SOP).